Futuristic Leadership to build a Golden Generation at Surakarta Elementary School - Dwi Maryani; Harun Joko Prayitno; Indri (CV. Creative Tugu Pena, 2024)
This research explores the application of futuristic leadership in SD Surakarta to build a golden generation. Futuristic leadership here refers to an approach that integrates technology, innovative curricula, sustainable teacher training, and community participation to create an adaptive and innovative educational environment. Research methods used include in-depth interviews, focus group discussions (FGD), participatory observations, and documentation analysis. Research results show that the application of technology in learning improves student engagement and motivation. Curriculum that combines project-based learning (PBL) and STEM approaches successfully enhances student creativity, critical thinking, collaboration, and problem-solving skills. Active participation of parents and communities creates strong support for student holistic development. Facilities and classrooms designed to support interactive and collaborative learning create an environment conducive to the development of students' skills and creativity. The impact of this application is a significant improvement in the academic achievement and skills of 21st century students, teacher satisfaction, as well as parental involvement. The research concludes that futuristic leadership in SD Surakarta is effective in building a golden generation and can serve as a model for other schools that want to adopt a similar approach.